Listen to the heart or mind first? Examining sequential coping mechanisms among Indians during the COVID-19 pandemic - Srivastava, Sanchita; Upadhaya, Puja; Jain, Renuka (Frontiers in Psychology, 2023)
The present study examines the mediating role of emotion-focused and problem-focused coping between stress and psychological well-being during the Covid-19 pandemic. The sample comprised 501(312 women and 184 men aged between 18 and 42) Indians who experienced the first-ever continued lockdown in India during the Covid-19 pandemic. The results of this study confirmed the presence of perceived stress due to the lockdown and pandemic among participants. Furthermore, perceived stress, coping including emotion-focused and problem-focused, and psychological well-being were found to be interrelated. The serial mediation analysis revealed that participants dealt with stress by choosing emotion-focused coping first as an immediate resort. After a reappraisal of stress-inducing situations, they used problem-focused coping, and this sequence of constant coping mechanisms helped maintain their psychological well-being. The findings of this study can be applied to develop strategies for people's mental health by public health organizations and health professionals.